Mixed Pine Forests in a Hotter and Drier World: The Great Resilience to Drought of Aleppo Pine Benefits It Over Other Coexisting Pine Species - Gazol, Antonio; Oliva, Jonàs; Valeriano, Cristina; Colangelo, Michele; Camarero, Jesús Julio (Frontiers in Forests and Global Change, 2022)
Drought is an important driver of forest dynamics in the Mediterranean region. The forecasted increase in drought frequency and severity can notably influence tree growth, forest structure, composition and productivity. Understanding how different coexisting tree species respond to drought is thus crucial to understand which are less vulnerable and will perform better in a warmer and drier world. To assess drought vulnerability, we used dendrochronology to study the radial growth trends and responses to a drought index of four pine species (Pinus halepensis, Pinus pinea, Pinus nigra and Pinus sylvestris) coexisting in North-eastern Spain. We reconstructed the growth of each species and evaluated short- and long-term growth response to drought of each species for the common period 1980–2017. The growth of the four pine species depended on water availability and high early-spring temperatures impacted the growth of P. nigra and P. sylvestris negatively. The occurrence of a severe drought between 2005 and 2007 lead to marked growth reductions in the four species, but it was greater in magnitude in P. pinea and P. halepensis in 2005, and in P. nigra in 2007. The results of BAI models at the individual tree level suggested that P. halepensis trees grow more than the rest of species. After accounting for age and drought effects, P. nigra and P. sylvestris displayed negative growth trends in the 2008–2017 period while P. pinea and P. halepensis displayed positive growth trends. P. sylvestris was the most resistant species and P. pinea the less resistant. Conversely, P. halepensis and P. pinea were slightly more resilient than P. sylvestris. Moreover, P. sylvestris was the species displaying the highest autocorrelation and the lowest coefficient of variation in ring-width indices. A marked drop in the autocorrelation of P. pinea ring-width indices was observed in response to the 2005 drought. These results indicate that all study species are vulnerable to drought but in different degrees. The strong resilience capacity of P. halepensis suggests that it will better thrive in a drier future, but mixed pine forests, such as the one here studied, may contract or become rare.